Use of colchicine in COVID-19 hospitalized patients - Emad E.A. Korra; Eman B AbdelFattah; Mervat A Ahmed (Egyptian Journal of Chest Disease and Tuberculosis, 2022)
Background COVID-19 has become a global public health challenge. Owing to a lack of knowledge about the virus, a significant number of potential targets for using a particular drug have been proposed. Colchicine is an old drug that has been widely used in autoimmune and inflammatory disorders. Aim The aim was to compare the effect of colchicine added to the standard of care treatment versus the standard of care treatment alone in hospitalized COVID-19 cases. Patients and methods This retrospective study was conducted on 100 patients who were admitted to Ain Shams University Field Hospital. Patients were divided to two equal groups: group A received colchicine plus the standard of care treatment, and group B received the standard of care treatment. Results Group A showed significant reduction in the duration of the constitutional symptoms and hospital stay. Group A showed significant reduction in ICU admission and the need for invasive mechanical ventilation. Furthermore, the mortality rate was significantly lower in group A. Conclusion Colchicine is a well-tolerated add-on treatment that significantly improved the constitutional symptoms, reduced the days of hospital stay, reduced the rate of ICU admission, reduced the need for mechanical ventilation, and also significantly improved the mortality rate.